Evaluation of the efficiency of the consolidation treatment with Paraloid B72, performed on artworks with degraded wood support - Ionescu Constantin Ştefan; Lunguleasa Aurel; Avram Anamaria; Spîrchez Cosmin (MATEC Web of Conferences, 2021)
The aim of the study is to determine the efficiency of the consolidation treatment with Paraloid B 72, performed on wood degraded by biological attack. The method of determining the HM hardness is an original scientific method, that is minimally invasive and which indicates the level of damage to the substrate before the consolidation treatment and at the end of consolidation, allowing the evaluation of the process. The specimens are tested with the Mark 10 apparatus to determine the HM hardness, which can be related to a standardized hardness. Two consolidation steps are performed in Paraloid B72, 12% solubilized in Mixture (Ethyl Acetate and Toluene, 1:1). At the end of the consolidation, the hardness increases from 6.74 N/mm2 (37.11%) to 13.73 N/mm2 (75.61%), compared to a reference wood, which has a hardness of 18.16 N/mm2.